2020
DOI: 10.2337/db19-0281
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Droplet Accumulation in Human Pancreatic Islets Is Dependent On Both Donor Age and Health

Abstract: Human but not mouse islets transplanted into immunodeficient NSG mice effectively accumulate lipid droplets (LDs). Because chronic lipid exposure is associated with islet β-cell dysfunction, we investigated LD accumulation in the intact human and mouse pancreas over a range of ages and states of diabetes. Very few LDs were found in normal human juvenile pancreatic acinar and islet cells, with numbers subsequently increasing throughout adulthood. While accumulation appeared evenly distributed in postjuvenile ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 46 publications
(60 reference statements)
7
52
0
Order By: Relevance
“…(II) Adipocyte infiltration in close proximity to the pancreatic islets in T2DM and hydrolysis of triglyceride content are other sources of fatty acids for the β-cells [ 65 , 85 ]. (III) Formation of lipid droplet within the β-cell was found in T2DM [ 86 ], and high expression of HSL in β-cell has decreased insulin secretion after feeding mice on a high fat diet, and this was associated with lower triglyceride accumulation within the islets of the transgenic mice compared with the wild-type mice [ 87 ]. Furthermore, toxic lipid intermediates derived from fatty acid metabolism including diacylglycerides and ceramides were confirmed to cause damage to insulin signaling within the hepatocytes and myocytes [ 88 , 89 ], but less is known about how such toxic metabolites can affect β-cells [ 7 , 57 ].…”
Section: Lipotoxicity and β-Cell Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…(II) Adipocyte infiltration in close proximity to the pancreatic islets in T2DM and hydrolysis of triglyceride content are other sources of fatty acids for the β-cells [ 65 , 85 ]. (III) Formation of lipid droplet within the β-cell was found in T2DM [ 86 ], and high expression of HSL in β-cell has decreased insulin secretion after feeding mice on a high fat diet, and this was associated with lower triglyceride accumulation within the islets of the transgenic mice compared with the wild-type mice [ 87 ]. Furthermore, toxic lipid intermediates derived from fatty acid metabolism including diacylglycerides and ceramides were confirmed to cause damage to insulin signaling within the hepatocytes and myocytes [ 88 , 89 ], but less is known about how such toxic metabolites can affect β-cells [ 7 , 57 ].…”
Section: Lipotoxicity and β-Cell Dysfunctionmentioning
confidence: 99%
“…It has been reported that lipid droplets are more common within acinar cells of human donors with T2DM [ 86 ], and higher expression of the CD36 fatty acid transporter protein was associated with defective insulin secretion [ 39 ]. Recently, we have demonstrated that remission of T2DM and recovery of β-cell function were associated with gradual normalization of the pancreas morphology ( Figure 3 ) [ 172 ].…”
Section: Intrapancretic Fat and Pancreas Morphologymentioning
confidence: 99%
“…The pancreas is roughly divided into pancreatic islets that secrete endocrine hormones such as insulin and glucagon, and exocrine regions that secrete digestive enzymes, and is composed of lobes separated by connective tissues. Pancreatic fat includes interlobular or intralobular infiltration of adipocytes [ 12 ] as well as accumulation of intracellular lipid droplets of pancreatic endocrine or exocrine cells [ 13 , 14 , 15 ]. So far, it has been said that pancreatic fat increases physiologically with age, obesity, diabetes mellitus, excess alcohol intake, and viral infections [ 14 , 16 , 17 ].…”
Section: Ectopic Fat In Pancreasmentioning
confidence: 99%
“…Pancreatic fat includes interlobular or intralobular infiltration of adipocytes [ 12 ] as well as accumulation of intracellular lipid droplets of pancreatic endocrine or exocrine cells [ 13 , 14 , 15 ]. So far, it has been said that pancreatic fat increases physiologically with age, obesity, diabetes mellitus, excess alcohol intake, and viral infections [ 14 , 16 , 17 ]. Fat accumulation in the pancreas is called pancreatic steatosis, fatty pancreas, etc.…”
Section: Ectopic Fat In Pancreasmentioning
confidence: 99%
“…One consequence of nutritional overload is the increased production of lipids including triglycerides (TG) that are stored in lipid droplets (LDs) (5). While the accumulation of LDs is closely tied to tissue dysfunction in non-alcoholic fatty liver disease, insulin resistant skeletal muscle, atherosclerosis, and diabetic cardiomyopathy, a role of LD under nutritional stress in b cell dysfunction has been underappreciated due to difficulty demonstrating LDs in mouse b cells (3,6,7). Importantly, LDs are easily identifiable in adult human b cells (6,8,9).…”
Section: Introductionmentioning
confidence: 99%